Wear-resistant corrosion-resistant refractory material for hazardous waste garbage incinerator and preparation method of wear-resistant corrosion-resistant refractory material
By preparing composite aerogels and refractory materials for activated silicon nitride fibers, the problem of insufficient wear resistance and lightweight in the prior art is solved, efficient thermal shock resistance and acid resistance are achieved, and the thermal efficiency and mechanical strength of the incinerator are improved.
Patent Information
- Application Number
- CN202411943510.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The wear-resistant lightweight refractory materials used in hazardous waste incinerators have shortcomings in wear resistance and lightweight performance. The thermal stability of starch adhesives is poor, resulting in poor wear resistance and lightweight effect of the material.
The composite aerogel and activated silicon nitride fiber are used as the main components to prepare nanocrystal liquid and high-temperature adhesives to form a porous structure refractory material. The activated silicon nitride fibers cooperate with the nanocrystal liquid obtained by hydrolysis of alumina to enhance the structural stability and bonding properties of the material.
It significantly improves the thermal shock resistance and acid resistance of the material, reduces the self-weight and thermal conductivity of the material, improves the thermal efficiency and mechanical properties of the incinerator, and enhances the thermal shock resistance and wear resistance of the material.
Smart Images

Figure BDA0005213101370000171
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of refractory materials, and in particular to a wear-resistant and corrosion-resistant refractory material for a hazardous waste incinerator and a preparation method thereof. Background Art
[0002] The development of wear-resistant lightweight refractory materials for hazardous waste incinerators has experienced continuous optimization from traditional refractory bricks to high-performance composite materials. In the early days, incinerators mainly used high-density refractory bricks. Although they had good refractoriness, they were heavy, had poor wear resistance, and had insufficient thermal shock resistance. They could not cope with the complex working conditions of high temperature, high corrosion, and high erosion in incinerators, resulting in rapid material loss and increased maintenance costs. With the improvement of incinerator processing capacity, lightweight refractory materials were gradually used in furnace linings. In the mid-20th century, high-aluminum and silicon lightweight materials were used to achieve weight reduction and improved thermal isolation performance, but the wear resistance and chemical corrosion resistance of these materials still needed to be improved.
[0003] The prior art CN108975887A discloses a refractory material, which comprises the following components by weight: 75-90 parts of aluminum oxide, 20-29 parts of silicon dioxide, 4-6 parts of nano aluminum oxide, 1-5 parts of metal toughening agent, and 3-5 parts of pore-forming agent. The metal toughening agent comprises metal powder or metal alloy powder. The excellent high temperature resistance of the aluminum oxide-silicon oxide system is utilized, and nano aluminum oxide, metal toughening agent, and pore-forming agent are added at the same time to reduce the sintering temperature, increase the toughness, enhance the good thermal insulation effect, and reduce the production cost.
[0004] However, the above patent content is to use starch adhesive as a pore-forming agent to bond materials and form pores to improve the thermal shock resistance of materials. However, starch adhesives have poor thermal stability, and the pore structure produced by pyrolysis is unstable and easy to fall off, so that the wear resistance of the material needs to be further improved. In addition, the material introduces a large amount of high-density high-temperature resistant materials and metal materials, resulting in the need to further improve the lightweight of the material. The excessively high dead weight places high requirements on the adhesive, which in turn leads to the need to further improve the performance of the functional adhesive material.
[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0006] The object of the present invention is to provide a wear-resistant and corrosion-resistant refractory material for a hazardous waste incinerator and a preparation method thereof, so as to solve the technical problem that the wear resistance and lightweight performance of refractory materials in the prior art need to be further improved.
[0007] The purpose of the present invention can be achieved by the following technical scheme: A wear-resistant and corrosion-resistant refractory material for a hazardous waste incinerator, comprising the following raw materials in parts by weight: 80-100 parts of high-aluminum aggregate, 15-20 parts of composite aerogel, 10-15 parts of high-temperature adhesive, and 9-15 parts of auxiliary materials;
[0008] The preparation method of the composite aerogel comprises the following steps:
[0009] A1. Add alumina powder and deionized water into a magnetic stirring kettle, stir at room temperature for 10-15 minutes, add ethylenediaminetetraacetic acid into the kettle, heat the kettle to 40-60°C, keep warm and stir for 1-2 hours to obtain nanocrystalline liquid;
[0010] The reaction principle for preparing nanocrystalline liquid is as follows: under the catalysis of acidic conditions, alumina powder is hydrolyzed to obtain an active structure, and finally a nanocrystalline liquid is prepared.
[0011] A2, after adding the nanocrystalline solution and activated silicon nitride fiber into the inner liner of the reactor, the inner liner of the reactor is sealed with a cover and then added into a stainless steel hydrothermal reactor, the stainless steel hydrothermal reactor is transferred into an oven, the oven temperature is increased to 220-240°C, the reaction is kept warm for 4-5 hours, and a composite gel is obtained by post-processing;
[0012] The reaction principle for preparing the composite gel is as follows: as the reaction proceeds, the active structures in the system undergo condensation reactions, and finally an Al-O-Al structure is generated. Thereafter, the chain segments in the system aggregate, cross-link, and combine with each other, becoming more and more abundant, and the molecular weight becomes larger and larger. Finally, when the critical point of the gel is reached, a gel is formed, and the internal three-dimensional network structure is gradually improved by the aggregation and cross-linking between the particles, and finally a composite gel is obtained through gel aging.
[0013] A3. The composite gel is post-treated in two steps to obtain a composite aerogel.
[0014] Furthermore, the auxiliary materials include water glass, boron nitride powder and steel fiber, the amount ratio of water glass, boron nitride powder and steel fiber is 3-5g:3-5g:3-5g, in step A1, the stirring rate of the magnetic stirring kettle is 60-80rpm, the amount ratio of alumina powder, deionized water and ethylenediaminetetraacetic acid is 3-4g:30-40mL:1-2mL; in step A2, the amount ratio of nanocrystalline liquid and silicon nitride oxide fiber is 5-6mL:1-2g, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reactor liner is taken out and the cover is opened, the reactor liner is transferred to a constant temperature drying oven, the temperature of the constant temperature drying oven is increased to 80-90°C, and the constant temperature treatment is performed for 1-2h to obtain a composite gel.
[0015] Furthermore, in step A3, the two-step post-treatment operation is as follows: immerse the composite gel in ethanol, let it stand for 12-16 hours, repeat the immersion three times, transfer the composite gel to a high-pressure reactor, increase the temperature of the high-pressure reactor to 40-50°C, introduce carbon dioxide gas into the high-pressure reactor, control the pressure to 12MPa, and treat at constant temperature and pressure for 2-3 hours to obtain a composite aerogel.
[0016] Furthermore, the preparation method of activated silicon nitride fiber comprises the following steps:
[0017] B1. Put silicon monoxide into a graphite crucible, place a graphite sheet on the top of the crucible, wrap the crucible with graphite paper, transfer the crucible to a high-temperature furnace, collect fibers attached to the graphite sheet after heat treatment, and obtain composite silicon nitride fibers;
[0018] The reaction equation for preparing silicon nitride fiber is:
[0019] 3SiO(g)+3C(s)+3N2(g)→Si3N4(s)+3CO(g)
[0020] 6SiO(g)+4N2(g)→Si3N4(s)+3CO(g)
[0021] The reaction principle for preparing silicon nitride fibers is as follows: silicon oxide sublimates at high temperatures and then reacts with carbon and nitrogen, ultimately preparing silicon nitride fibers on the surface of a graphite sheet.
[0022] B2. Add the composite silicon nitride fiber and 98.0wt% sulfuric acid into a reactor at a temperature of 0-5°C. After stirring for 10-15 minutes, add sodium chlorate into the reactor. Keep the temperature of the reactor at 0-5°C for 2-4 hours. Post-treat to obtain activated silicon nitride fiber.
[0023] The principle of preparing activated silicon nitride fiber is as follows: multi-layer graphene undergoes partial sulfation reaction, making the structure of graphene more active and creating conditions for oxidation reaction. Sodium chlorate will decompose to produce chloric acid and oxygen under acidic conditions. The strong oxidizing effect of chloric acid can oxidize the carbon layer of graphene to produce graphene oxide, which contains various oxygen functional groups, such as epoxy groups, carboxyl groups and hydroxyl groups.
[0024] Furthermore, in step B1, the heat treatment operation is as follows: after nitrogen is introduced into the high-temperature furnace, the temperature is increased to 1800-2000°C at a heating rate of 6-8°C / min, and the reaction is kept warm for 1-2h, and then naturally cooled to room temperature to complete the heat treatment operation; in step B2, the amount ratio of the composite silicon nitride fiber, 98.0wt% sulfuric acid and sodium chlorate is 5-6g:50-60mL:3-5g, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is increased to room temperature, and the pH of the reaction system is adjusted to 7 with acetic acid, and the reaction liquid is filtered to collect the filter cake, and the filter cake is washed 3-5 times with anhydrous ethanol and deionized water, and then the filter cake is transferred to a drying oven at a temperature of 60°C and vacuum dried to constant weight to obtain activated silicon nitride fiber.
[0025] Furthermore, the preparation method of the high temperature adhesive comprises the following steps:
[0026] C1. Add 2,4,6,8-tetramethyl-2-[3-(oxiranylmethoxy)propyl]cyclotetrasiloxane, 3-(methacryloyloxy)propyltrimethoxysilane, epoxy vinyl resin, chloroplatinic acid hexahydrate and N,N-dimethylformamide into a reaction kettle, increase the temperature of the reaction kettle to 40-50° C., keep the temperature for reaction for 1-2 hours, and perform post-treatment to obtain a composite resin;
[0027] The reaction principle for preparing the composite resin is as follows: under the initiation of a catalyst, the silicon-hydrogen bonds on 2,4,6,8-tetramethyl-2-[3-(oxiranylmethoxy)propyl]cyclotetrasiloxane react with the double bonds on 3-(methacryloyloxy)propyltrimethoxysilane and epoxy vinyl resin to undergo silicon-hydrogen addition reaction, and finally the composite resin is prepared.
[0028] C2. Add the composite resin, silicone resin and N,N-dimethylformamide into the reactor. After the temperature of the reactor is lowered to 0-5°C, add saturated sodium hydroxide solution dropwise into the reactor. After keeping the temperature for 1-2 hours, adjust the pH value of the system to 7 with glacial acetic acid, and obtain the adhesive precursor by post-treatment.
[0029] The reaction principle for preparing the adhesive precursor is: under alkaline conditions, the silane coupling agent component in the composite resin is hydrolyzed and cross-linked with the siloxane structure in the silicone resin to obtain the adhesive precursor.
[0030] C3. The adhesive precursor, the composite silicon nitride fiber and the activated silicon nitride fiber are mixed evenly and then added into a twin-screw extruder to extrude to obtain a high-temperature adhesive.
[0031] Furthermore, in step C1, the amount ratio of 2,4,6,8-tetramethyl-2-[3-(oxiranylmethoxy)propyl]cyclotetrasiloxane, 3-(methacryloyloxy)propyltrimethoxysilane, epoxy vinyl resin, chloroplatinic acid hexahydrate and N,N-dimethylformamide is 8-10g:3-4g:10-15g:0.1-0.2g:80-100mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction solution is transferred to a rotary evaporator at a temperature of 80-90°C, and the solvent is evaporated under reduced pressure to obtain a composite resin.
[0032] Furthermore, in step C2, the amount ratio of the composite resin, the silicone resin, N,N-dimethylformamide and the saturated sodium hydroxide solution is 3-4g:5-8g:30-40mL:0.1-0.2mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction solution is transferred to a rotary evaporator at a temperature of 80-90°C, and the solvent is evaporated under reduced pressure to obtain an adhesive precursor.
[0033] Furthermore, in step C3, the usage ratio of the adhesive precursor, the composite silicon nitride fiber and the activated silicon nitride fiber is 8-10 g:1 g:1 g, and the pressure of the twin-screw extruder is set to 40-60 Bar.
[0034] Furthermore, the preparation method of high-alumina aggregate is as follows: high-alumina bauxite is crushed through a 400-600 mesh sieve, mixed with nanocrystalline liquid, and then transferred to a tubular furnace, and calcined to obtain high-alumina aggregate.
[0035] Furthermore, the dosage ratio of high-alumina bauxite and nanocrystalline liquid is 2-3g:1mL, and the calcination operation is as follows: after nitrogen protection is introduced into the tubular furnace, the tubular furnace is heated to 1350-1600°C at a heating rate of 5-8°C / min, the reaction is kept warm for 4-6h, and naturally cooled to room temperature to obtain high-alumina aggregate.
[0036] The present invention also proposes a method for preparing wear-resistant, corrosion-resistant and refractory materials for hazardous waste incinerators, comprising the following steps: adding high-aluminum aggregate, boron nitride powder and steel fiber into a twin-screw extruder, gradually adding composite aerogel, high-temperature adhesive and water glass into the mixture during stirring, setting the pressure of the twin-screw extruder to 80-100 bar, and obtaining the wear-resistant, corrosion-resistant and refractory materials after twin-screw extrusion.
[0037] The present invention has the following beneficial effects:
[0038] 1. The present invention prepares composite silicon nitride fiber and activated silicon nitride fiber, and the activated silicon nitride fiber cooperates with the nanocrystalline liquid obtained by hydrolyzing alumina to prepare the composite aerogel. After the composite aerogel fills the material structure, the weight of the material itself is significantly reduced, thereby reducing the burden on the incinerator structure. The porous structure of the aerogel also reduces the thermal conductivity of the material, thereby reducing heat loss and improving the thermal efficiency of the incinerator. The reduction of the porous material of the aerogel and the weight of the material itself further improves the thermal shock resistance of the material. The composite silicon nitride fiber serves as a supporting skeleton at high temperature, and the active groups on the activated silicon nitride fiber react with the resin component of the high-temperature adhesive at high temperature to prevent further shrinkage of the high-temperature adhesive, and finally significantly improve the thermal shock resistance of the material. The nano-alumina particles in the nanocrystalline liquid fill the defects of the crystal form of the calcined product during the calcination of high-alumina bauxite, and finally stabilize the structure of the high-alumina aggregate of the final product, thereby significantly improving the acid resistance, mechanical properties and thermal shock resistance of the material.
[0039] 2. The present invention prepares activated silicon nitride fibers as the skeleton structure of alumina aerogel to obtain composite aerogel, thereby overcoming the defect of low mechanical properties of aerogel materials, and the alumina and silicon nitride components significantly improve the high temperature resistance of the composite aerogel; utilizing the extremely low thermal conductivity of aerogel, the thermal conductivity of the material is significantly reduced in the composite aerogel material, making it more effective in isolating heat, reducing heat energy loss, and improving the thermal efficiency of the incinerator; the thermal stability and low thermal expansion coefficient of the composite aerogel, when used in combination with other materials, help to reduce the thermal stress caused by temperature fluctuations inside the material, thereby reducing the formation of cracks and improving the thermal shock resistance of the material.
[0040] 3. The present invention selects cyclic siloxane as a cross-linking structure, adds a silane coupling agent and an epoxy resin to finally prepare a composite resin, combines the stability of the cyclic structure with the high viscosity of the epoxy resin, and uses a silane coupling agent as a cross-linking agent to cross-link with the silicone resin and dope with composite silicon nitride fiber and activated silicon nitride fiber to obtain a corrosion-resistant and wear-resistant high-temperature adhesive; the high-temperature adhesive effectively improves the initial mechanical strength of the refractory material, keeps the material structurally stable during the manufacturing and installation process, prevents damage or rupture caused by stress or external force at high temperature, and effectively reduces the thermal stress caused by drastic temperature changes. By providing uniform bonding between the refractory materials, they help to disperse the thermal stress, thereby enhancing the thermal shock resistance of the material. DETAILED DESCRIPTION
[0041] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] The epoxy vinyl resin used in the present invention is purchased from Guiyang Jinhua Heng Chemical Co., Ltd.
[0043] The organic silicon resin used in the present invention is purchased from Changzhou Jianuo Organic Silicone Co., Ltd., with the product number of FJN-1152.
[0044] Example 1
[0045] This embodiment provides a method for preparing activated silicon nitride fiber for wear-resistant, corrosion-resistant and refractory materials for hazardous waste incinerators, comprising the following steps:
[0046] Step 1: Preparation of activated silicon nitride fibers
[0047] Weigh: 100.0g of silicon monoxide is loaded into a graphite crucible, a graphite sheet is placed on the top of the crucible, and the crucible is wrapped with graphite paper, and then the crucible is transferred to a high-temperature furnace. After nitrogen is introduced into the high-temperature furnace, the temperature is increased to 1800°C at a heating rate of 6°C / min. After the reaction is kept warm for 1h, it is naturally cooled to room temperature, and the fibers attached to the graphite sheet are collected to obtain composite silicon nitride fibers.
[0048] Step 2: Preparation of activated silicon nitride fibers
[0049] Weigh: 500.0g of composite silicon nitride fiber and 5.0L98.0wt% sulfuric acid are added to a reactor at a temperature of 5°C. After stirring for 10 minutes, 300.0g of sodium chlorate is added to the reactor. The temperature of the reactor is maintained at 5°C for 2 hours. After the reaction is completed, the temperature of the reactor is raised to room temperature. After adjusting the pH of the reaction system to 7 with acetic acid, the reaction liquid is filtered to collect the filter cake. After washing the filter cake 3 times with anhydrous ethanol and deionized water, the filter cake is transferred to a drying oven at a temperature of 60°C and vacuum dried to constant weight to obtain activated silicon nitride fiber.
[0050] Example 2
[0051] This embodiment provides a method for preparing activated silicon nitride fiber for wear-resistant, corrosion-resistant and refractory materials for hazardous waste incinerators, comprising the following steps:
[0052] Step 1: Preparation of activated silicon nitride fibers
[0053] Weigh: 100.0g of silicon monoxide is loaded into a graphite crucible, a graphite sheet is placed on the top of the crucible, and the crucible is wrapped with graphite paper, and then the crucible is transferred to a high-temperature furnace. After nitrogen is introduced into the high-temperature furnace, the temperature is increased to 2000°C at a heating rate of 8°C / min. After the reaction is kept warm for 2h, it is naturally cooled to room temperature, and the fibers attached to the graphite sheet are collected to obtain composite silicon nitride fibers.
[0054] Step 2: Preparation of activated silicon nitride fibers
[0055] Weigh: 600.0g of composite silicon nitride fiber and 6.0L98.0wt% sulfuric acid are added to a reactor at a temperature of 0°C. After stirring for 15 minutes, 500.0g of sodium chlorate is added to the reactor. The temperature of the reactor is maintained at 0°C for 4 hours. After the reaction is completed, the temperature of the reactor is raised to room temperature. After adjusting the pH of the reaction system to 7 with acetic acid, the reaction liquid is filtered to collect the filter cake. After washing the filter cake 5 times with anhydrous ethanol and deionized water, the filter cake is transferred to a drying oven at a temperature of 60°C and vacuum dried to constant weight to obtain activated silicon nitride fiber.
[0056] Example 3
[0057] This embodiment provides a method for preparing activated silicon nitride fiber for wear-resistant, corrosion-resistant and refractory materials for hazardous waste incinerators, comprising the following steps:
[0058] Step 1: Preparation of activated silicon nitride fibers
[0059] Weigh: 100.0g of silicon monoxide is loaded into a graphite crucible, a graphite sheet is placed on the top of the crucible, and the crucible is wrapped with graphite paper, and then the crucible is transferred to a high-temperature furnace. After nitrogen is introduced into the high-temperature furnace, the temperature is increased to 1900°C at a heating rate of 7°C / min. After the reaction is kept warm for 2h, it is naturally cooled to room temperature, and the fibers attached to the graphite sheet are collected to obtain composite silicon nitride fibers.
[0060] Step 2: Preparation of activated silicon nitride fibers
[0061] Weigh: 550.0g of composite silicon nitride fiber and 5.5L98.0wt% sulfuric acid are added to a reactor at a temperature of 3°C. After stirring for 12 minutes, 400.0g of sodium chlorate is added to the reactor. The temperature of the reactor is maintained at 3°C for 3 hours. After the reaction is completed, the temperature of the reactor is raised to room temperature. After adjusting the pH of the reaction system to 7 with acetic acid, the reaction liquid is filtered to collect the filter cake. After washing the filter cake 4 times with anhydrous ethanol and deionized water, the filter cake is transferred to a drying oven at a temperature of 60°C and vacuum dried to constant weight to obtain activated silicon nitride fiber.
[0062] Example 4
[0063] This embodiment provides a method for preparing a high-temperature adhesive for wear-resistant, corrosion-resistant and refractory materials for hazardous waste incinerators, comprising the following steps:
[0064] Step 1: Preparation of composite resin
[0065] Weigh: 800.0g 2,4,6,8-tetramethyl-2-[3-(oxiranylmethoxy)propyl]cyclotetrasiloxane, 300.0g 3-(methacryloyloxy)propyltrimethoxysilane, 1.0kg epoxy vinyl resin, 10.0g chloroplatinic acid hexahydrate and 8.0L N,N-dimethylformamide and add them into a reactor. The temperature of the reactor is raised to 50°C and kept warm for 2h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction solution is transferred to a rotary evaporator at 80°C, and the solvent is evaporated under reduced pressure to obtain a composite resin.
[0066] Step ②: Preparation of adhesive precursor
[0067] Weigh: 300.0g of composite resin, 500.0g of silicone resin and 3.0L of N,N-dimethylformamide and add them to the reactor. After the temperature of the reactor is reduced to 5°C, 10.0mL of saturated sodium hydroxide solution is added dropwise to the reactor. After the reaction is kept warm for 1h, glacial acetic acid is used to adjust the pH of the system to 7. After the reaction is completed, wait for the temperature of the reactor to be reduced to room temperature, transfer the reaction solution to a rotary evaporator at 80°C, and evaporate the solvent under reduced pressure to obtain an adhesive precursor.
[0068] Step 3: Preparation of high temperature adhesive
[0069] Weigh: 800.0 g of adhesive precursor, 100.0 g of the composite silicon nitride fiber prepared in Example 1, and 100.0 g of the activated silicon nitride fiber prepared in Example 1, mix them evenly, and add them into a twin-screw extruder. The pressure of the twin-screw extruder is set to 40 Bar, and extrude to obtain a high-temperature adhesive.
[0070] Example 5
[0071] This embodiment provides a method for preparing a high-temperature adhesive for wear-resistant, corrosion-resistant and refractory materials for hazardous waste incinerators, comprising the following steps:
[0072] Step 1: Preparation of composite resin
[0073] Weigh: 1.0 kg 2,4,6,8-tetramethyl-2-[3-(oxiranylmethoxy)propyl]cyclotetrasiloxane, 400.0 g 3-(methacryloyloxy)propyltrimethoxysilane, 1.5 kg epoxy vinyl resin, 20.0 g chloroplatinic acid hexahydrate and 10.0 L N, N-dimethylformamide and add them into a reactor. The temperature of the reactor is raised to 50°C and kept warm for 2 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction solution is transferred to a rotary evaporator at 90°C, and the solvent is evaporated under reduced pressure to obtain a composite resin.
[0074] Step ②: Preparation of adhesive precursor
[0075] Weigh: 400.0g of composite resin, 800.0g of silicone resin and 4.0L of N,N-dimethylformamide and add them to the reactor. After the temperature of the reactor is reduced to 0°C, 20.0mL of saturated sodium hydroxide solution is added dropwise to the reactor. After the reaction is kept warm for 2h, glacial acetic acid is used to adjust the pH of the system to 7. After the reaction is completed, wait for the temperature of the reactor to be reduced to room temperature, transfer the reaction solution to a rotary evaporator at 90°C, and evaporate the solvent under reduced pressure to obtain an adhesive precursor.
[0076] Step 3: Preparation of high temperature adhesive
[0077] Weigh: 1.0 kg of adhesive precursor, 100.0 g of the composite silicon nitride fiber prepared in Example 2, and 100.0 g of the activated silicon nitride fiber prepared in Example 2, mix them evenly, and add them into a twin-screw extruder. The pressure of the twin-screw extruder is set to 60 Bar, and a high-temperature adhesive is extruded.
[0078] Example 6
[0079] This embodiment provides a method for preparing a high-temperature adhesive for wear-resistant, corrosion-resistant and refractory materials for hazardous waste incinerators, comprising the following steps:
[0080] Step 1: Preparation of composite resin
[0081] Weigh: 900.0g 2,4,6,8-tetramethyl-2-[3-(oxiranylmethoxy)propyl]cyclotetrasiloxane, 350.0g 3-(methacryloyloxy)propyltrimethoxysilane, 1.2kg epoxy vinyl resin, 15.0g chloroplatinic acid hexahydrate and 9.0L N,N-dimethylformamide and add them into a reactor. The temperature of the reactor is raised to 45°C and kept warm for 2h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction solution is transferred to a rotary evaporator at a temperature of 85°C, and the solvent is evaporated under reduced pressure to obtain a composite resin.
[0082] Step ②: Preparation of adhesive precursor
[0083] Weigh: 350.0g of composite resin, 650.0g of silicone resin and 3.5L of N,N-dimethylformamide and add them into the reactor. After the temperature of the reactor is reduced to 3°C, 15.0mL of saturated sodium hydroxide solution is added dropwise to the reactor. After the reaction is kept warm for 2h, glacial acetic acid is used to adjust the pH of the system to 7. After the reaction is completed, wait for the temperature of the reactor to be reduced to room temperature, transfer the reaction solution to a rotary evaporator at a temperature of 85°C, and evaporate the solvent under reduced pressure to obtain an adhesive precursor.
[0084] Step 3: Preparation of high temperature adhesive
[0085] Weigh: 900.0 g of adhesive precursor, 100.0 g of the composite silicon nitride fiber prepared in Example 3, and 100.0 g of the activated silicon nitride fiber prepared in Example 3, mix them evenly, and add them into a twin-screw extruder. The pressure of the twin-screw extruder is set to 50 Bar, and extrude to obtain a high-temperature adhesive.
[0086] Example 7
[0087] This embodiment provides a method for preparing a composite aerogel for wear-resistant, corrosion-resistant and refractory materials for hazardous waste incinerators, comprising the following steps:
[0088] Step (1): Preparation of nanocrystalline liquid
[0089] Weigh: 300.0g of alumina powder and 3.0L of deionized water are added to a magnetic stirring kettle at a stirring rate of 60rpm. After stirring at room temperature for 10min, 100.0mL of ethylenediaminetetraacetic acid is added to the reactor. The temperature of the reactor is raised to 40°C and stirred for 1h to obtain a nanocrystalline liquid.
[0090] Step (2): preparing composite gel
[0091] Weigh: 500.0 mL of nanocrystal solution and 200.0 g of activated silicon nitride fiber prepared in Example 1 are added to the inner liner of the reactor, the reactor liner is sealed with a cover and then added to a stainless steel hydrothermal reactor, the stainless steel hydrothermal reactor is transferred to the inside of an oven, the oven temperature is increased to 220° C., and the reaction is kept warm for 4 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reactor liner is taken out and the cover is opened, the reactor liner is transferred to a constant temperature drying oven, the temperature of the constant temperature drying oven is increased to 80° C., and the constant temperature treatment is performed for 1 hour to obtain a composite gel.
[0092] Step (3): preparing composite aerogel
[0093] Weigh: 1.0 kg of the composite gel was soaked in ethanol and allowed to stand for 12 h. After repeating the soaking three times, the composite gel was transferred to a high-pressure reactor. After the temperature of the high-pressure reactor was increased to 40°C, carbon dioxide gas was introduced into the high-pressure reactor, the pressure was controlled to be 12 MPa, and the mixture was treated at constant temperature and pressure for 2 h to obtain a composite aerogel.
[0094] Example 8
[0095] This embodiment provides a method for preparing a composite aerogel for wear-resistant, corrosion-resistant and refractory materials for hazardous waste incinerators, comprising the following steps:
[0096] Step (1): Preparation of nanocrystalline liquid
[0097] Weigh: 400.0g of alumina powder and 4.0L of deionized water are added into a magnetic stirring kettle at a stirring rate of 80rpm. After stirring at room temperature for 15min, 200.0mL of ethylenediaminetetraacetic acid is added into the reactor. The temperature of the reactor is raised to 60°C and stirred for 2h to obtain a nanocrystalline liquid.
[0098] Step (2): preparing composite gel
[0099] Weigh: 600.0 mL of nanocrystal solution and 200.0 g of activated silicon nitride fiber prepared in Example 2 are added to the inner liner of the reactor, and then the inner liner of the reactor is sealed with a cover and added to a stainless steel hydrothermal reactor. The stainless steel hydrothermal reactor is transferred to the inside of an oven, the oven temperature is increased to 240°C, and the reaction is kept warm for 5 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the inner liner of the reactor is taken out and the cover is opened, and the inner liner of the reactor is transferred to a constant temperature drying oven. The temperature of the constant temperature drying oven is increased to 90°C, and the constant temperature treatment is performed for 2 hours to obtain a composite gel.
[0100] Step (3): preparing composite aerogel
[0101] Weigh: 1.0 kg of the composite gel was soaked in ethanol and allowed to stand for 16 hours. After repeating the soaking three times, the composite gel was transferred to a high-pressure reactor. After the temperature of the high-pressure reactor was increased to 50°C, carbon dioxide gas was introduced into the high-pressure reactor, the pressure was controlled to be 12 MPa, and the temperature and pressure were kept constant for 3 hours to obtain a composite aerogel.
[0102] Example 9
[0103] This embodiment provides a method for preparing a composite aerogel for wear-resistant, corrosion-resistant and refractory materials for hazardous waste incinerators, comprising the following steps:
[0104] Step (1): Preparation of nanocrystalline liquid
[0105] Weigh: 350.0g of alumina powder and 3.5L of deionized water are added to a magnetic stirring kettle at a stirring rate of 70rpm. After stirring at room temperature for 12min, 150.0mL of ethylenediaminetetraacetic acid is added to the reactor. The temperature of the reactor is raised to 50°C and stirred for 2h to obtain a nanocrystalline liquid.
[0106] Step (2): preparing composite gel
[0107] Weigh: 550.0 mL of nanocrystal solution and 150.0 g of activated silicon nitride fiber prepared in Example 3, add them to the inner liner of the reactor, seal the inner liner of the reactor with a cover and add them to a stainless steel hydrothermal reactor, transfer the stainless steel hydrothermal reactor to the inside of an oven, increase the oven temperature to 230°C, and keep the reaction warm for 5 hours. After the reaction is completed, wait for the temperature of the reactor to drop to room temperature, take out the inner liner of the reactor and open the cover, transfer the inner liner of the reactor to a constant temperature drying oven, increase the temperature of the constant temperature drying oven to 85°C, and treat at the constant temperature for 2 hours to obtain a composite gel.
[0108] Step (3): preparing composite aerogel
[0109] Weigh: 1.0 kg of the composite gel was soaked in ethanol and allowed to stand for 14 h. After repeating the soaking three times, the composite gel was transferred to a high-pressure reactor. After the temperature of the high-pressure reactor was increased to 45°C, carbon dioxide gas was introduced into the high-pressure reactor, the pressure was controlled to be 12 MPa, and the temperature and pressure were kept constant for 3 h to obtain a composite aerogel.
[0110] Example 10
[0111] This embodiment provides a method for preparing a wear-resistant and corrosion-resistant refractory material for a hazardous waste incinerator, comprising the following steps:
[0112] S1. Preparation of high alumina aggregate
[0113] Weigh: 200.0 g of high-alumina bauxite was crushed through a 600-mesh sieve, mixed with 100.0 mL of the nanocrystalline liquid prepared in Example 7, and transferred to a tubular furnace. After nitrogen protection was introduced, the tubular furnace was heated to 1350° C. at a heating rate of 5° C. / min, kept warm for 4 hours, and naturally cooled to room temperature to obtain a high-alumina aggregate.
[0114] S2. Preparation of wear-resistant and corrosion-resistant refractory materials
[0115] Weigh: 800.0g of high-alumina aggregate, 30.0g of boron nitride powder and 30.0g of steel fiber and add them to a twin-screw extruder. During the stirring process, 150.0g of the composite aerogel prepared in Example 7, 100.0g of the high-temperature adhesive prepared in Example 4 and 30.0g of water glass are gradually added to the mixture. The pressure of the twin-screw extruder is set to 80bar, and after twin-screw extrusion, a wear-resistant, corrosion-resistant and refractory material is obtained.
[0116] Embodiment 11
[0117] This embodiment provides a method for preparing a wear-resistant and corrosion-resistant refractory material for a hazardous waste incinerator, comprising the following steps:
[0118] S1. Preparation of high alumina aggregate
[0119] Weigh: 300.0 g of high-alumina bauxite was crushed through a 400-mesh sieve, mixed with 100.0 mL of the nanocrystalline liquid prepared in Example 8, and transferred to a tubular furnace. After nitrogen protection was introduced, the tubular furnace was heated to 1600° C. at a heating rate of 8° C. / min, kept warm for 6 hours, and naturally cooled to room temperature to obtain a high-alumina aggregate.
[0120] S2. Preparation of wear-resistant and corrosion-resistant refractory materials
[0121] Weigh: 1.0 kg of high-alumina aggregate, 50.0 g of boron nitride powder and 50.0 g of steel fiber and add them to a twin-screw extruder. During the stirring process, 200.0 g of the composite aerogel prepared in Example 8, 150.0 g of the high-temperature adhesive prepared in Example 5 and 50.0 g of water glass are gradually added to the mixture. The pressure of the twin-screw extruder is set to 100 bar. After twin-screw extrusion, a wear-resistant, corrosion-resistant and refractory material is obtained.
[0122] Example 12
[0123] This embodiment provides a method for preparing a wear-resistant and corrosion-resistant refractory material for a hazardous waste incinerator, comprising the following steps:
[0124] S1. Preparation of high alumina aggregate
[0125] Weigh: 250.0 g of high-alumina bauxite was crushed through a 500-mesh sieve, mixed with 100.0 mL of the nanocrystalline liquid prepared in Example 9, and transferred to a tubular furnace. After nitrogen protection was introduced, the tubular furnace was heated to 1500° C. at a heating rate of 6° C. / min, kept warm for 6 hours, and naturally cooled to room temperature to obtain a high-alumina aggregate.
[0126] S2. Preparation of wear-resistant and corrosion-resistant refractory materials
[0127] Weigh: 900.0g of high-alumina aggregate, 40.0g of boron nitride powder and 40.0g of steel fiber and add them to a twin-screw extruder. During the stirring process, 180.0g of the composite aerogel prepared in Example 9, 120.0g of the high-temperature adhesive prepared in Example 6 and 40.0g of water glass are gradually added to the mixture. The pressure of the twin-screw extruder is set to 90bar, and after twin-screw extrusion, a wear-resistant, corrosion-resistant and refractory material is obtained.
[0128] Comparative Example 1
[0129] The difference between this comparative example and Example 12 is that in the preparation process of the composite aerogel used in step S2, the composite silicon nitride fibers prepared in Example 3 are used in equal amounts to replace the activated silicon nitride fibers prepared in Example 3.
[0130] Comparative Example 2
[0131] The difference between this comparative example and Example 12 is that in the process of preparing the high-temperature adhesive used in step S2, the composite silicon nitride fiber prepared in Example 3 and the activated silicon nitride fiber prepared in Example 3 are omitted.
[0132] Comparative Example 3
[0133] The difference between this comparative example and Example 12 is that in step S1, the use of nanocrystalline liquid is eliminated.
[0134] Comparative Example 4
[0135] The difference between this comparative example and Example 12 is that in step S2, an equal amount of silicon nitride fibers is used to replace the composite aerogel.
[0136] Performance Test:
[0137] Referring to the standard GB / T 23294-2021 "Wear-resistant refractory materials", the wear-resistant and corrosion-resistant refractory materials prepared in Examples 10-12 and Comparative Examples 1-3 were tested for room temperature wear resistance, room temperature flexural strength, room temperature compressive strength, thermal shock resistance times (1000°C / water cooling), bulk density, and thermal conductivity;
[0138] The acid resistance of the wear-resistant and corrosion-resistant refractory materials prepared in Examples 10-12 and Comparative Examples 1-3 was tested with reference to the standard GB / T 17601-2023 “Test method for acid resistance of refractory materials”. The specific data are shown in Table 1.
[0139] Table 1-Performance test data of each sample
[0140]
[0141] Data Analysis:
[0142] By comparing and analyzing the data in Table 1 above, the wear resistance of the wear-resistant and corrosion-resistant refractory material prepared by the present invention is 3.8 cm 3 , room temperature flexural strength 17.0MPa, room temperature compressive strength 125.4MPa, thermal shock resistance (1000℃ / water cooling) 34 times, bulk density 2.48g / cm 3 And the acid resistance is 99.8%;
[0143] By comparing the data of Example 12 and Comparative Example 1, it can be found that the mechanical properties, thermal shock resistance and acid resistance of the material are significantly reduced, indicating that the large number of active functional groups on the surface of the activated silicon nitride fiber promote the cross-linking of the composite aerogel and the high-temperature adhesive during the bonding process with the high-temperature adhesive, and ultimately make the structure of the material more compact, so that the mechanical properties and acid resistance of the material are significantly improved;
[0144] By comparing the data of Example 12 and Comparative Example 2, it can be found that the number of thermal shock resistance of the material is significantly reduced, indicating that the composite silicon nitride fiber acts as a supporting skeleton at high temperature, and the active groups on the activated silicon nitride fiber react with the resin component of the high-temperature adhesive at high temperature to prevent further shrinkage of the high-temperature adhesive, and ultimately significantly improve the thermal shock resistance of the material;
[0145] By comparing the data of Example 12 and Comparative Example 3, it can be found that the mechanical properties and thermal shock resistance of the material are significantly reduced, indicating that the nano-alumina particles in the nano-crystalline liquid fill the defects of the calcined product crystal form during the calcination of high-alumina bauxite, and finally make the final product high-alumina aggregate structure stable, thereby significantly improving the mechanical properties and thermal shock resistance of the material;
[0146] By comparing the data of Example 12 and Comparative Example 4, it can be found that the thermal shock resistance and density of the material are significantly reduced, and the thermal conductivity is significantly improved, which shows that after the composite aerogel fills the material structure, the weight of the material itself is significantly reduced, thereby reducing the burden on the incinerator structure. The porous structure of the aerogel also reduces the thermal conductivity of the material, thereby reducing heat loss and improving the thermal efficiency of the incinerator. In addition, the porous structure of the aerogel and the reduction of the weight of the material itself further improve the thermal shock resistance of the material.
[0147] It is explained that the present invention is prepared by preparing composite silicon nitride fibers and activated silicon nitride fibers, the latter are synergistically coordinated with nanocrystalline liquid to prepare composite aerogel, and the two act as high-temperature adhesive skeletons to enhance the high-temperature resistance of the high-temperature adhesive. The nanocrystalline liquid is also used as an additive to repair the crystal defects of the material during the high-temperature calcination of high-alumina bauxite. Finally, a wear-resistant, mechanically strong and acid-resistant lightweight thermal insulation, wear-resistant and corrosion-resistant refractory material is prepared by mixing high-alumina aggregate, composite aerogel, high-temperature adhesive and auxiliary materials.
[0148] The above are only examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they are all within the protection scope of the present invention.
Claims
1. A wear-resistant and corrosion-resistant refractory material for a hazardous waste incinerator, characterized in that: The raw material composition includes the following parts by weight: 80-100 parts of high-aluminum aggregate, 15-20 parts of composite aerogel, 10-15 parts of high-temperature adhesive, and 9-15 parts of auxiliary materials; The preparation method of the composite aerogel comprises the following steps: A1. Add alumina powder and deionized water into a magnetic stirring kettle, stir at room temperature for 10-15 minutes, add ethylenediaminetetraacetic acid into the kettle, heat the kettle to 40-60°C, keep warm and stir for 1-2 hours to obtain nanocrystalline liquid; A2, after adding the nanocrystalline solution and activated silicon nitride fiber into the inner liner of the reactor, the inner liner of the reactor is sealed with a cover and then added into a stainless steel hydrothermal reactor, the stainless steel hydrothermal reactor is transferred into an oven, the oven temperature is increased to 220-240°C, the reaction is kept warm for 4-5 hours, and a composite gel is obtained by post-processing; A3. The composite gel is post-treated in two steps to obtain a composite aerogel.
2. The wear-resistant and corrosion-resistant refractory material for hazardous waste incinerator according to claim 1 is characterized in that: The auxiliary materials include water glass, boron nitride powder and steel fiber, the dosage ratio of water glass, boron nitride powder and steel fiber is 3-5g:3-5g:3-5g, in step A1, the stirring rate of the magnetic stirring kettle is 60-80rpm, the dosage ratio of alumina powder, deionized water and ethylenediaminetetraacetic acid is 3-4g:30-40mL:1-2mL; in step A2, the dosage ratio of nanocrystalline liquid and silicon nitride oxide fiber is 5-6mL:1-2g.
3. The wear-resistant and corrosion-resistant refractory material for hazardous waste incinerator according to claim 1, characterized in that: In step A3, the two-step post-treatment operation is as follows: immerse the composite gel in ethanol, let it stand for 12-16 hours, repeat the immersion three times, transfer the composite gel to a high-pressure reactor, increase the temperature of the high-pressure reactor to 40-50°C, introduce carbon dioxide gas into the high-pressure reactor, control the pressure to 12MPa, and treat at constant temperature and pressure for 2-3 hours to obtain a composite aerogel.
4. The wear-resistant and corrosion-resistant refractory material for hazardous waste incinerator according to claim 1, characterized in that: The preparation method of the activated silicon nitride fiber comprises the following steps: B1. Put silicon monoxide into a graphite crucible, place a graphite sheet on the top of the crucible, wrap the crucible with graphite paper, transfer the crucible to a high-temperature furnace, collect fibers attached to the graphite sheet after heat treatment, and obtain composite silicon nitride fibers; B2. Add the composite silicon nitride fiber and 98.0wt% sulfuric acid into a reactor at a temperature of 0-5°C. After stirring for 10-15 minutes, add sodium chlorate into the reactor. Keep the temperature of the reactor at 0-5°C for 2-4 hours, and then post-treat to obtain activated silicon nitride fiber.
5. The wear-resistant and corrosion-resistant refractory material for hazardous waste incinerator according to claim 4, characterized in that: In step B1, the heat treatment operation is as follows: after nitrogen is introduced into the high-temperature furnace, the temperature is increased to 1800-2000°C at a heating rate of 6-8°C / min, and after the reaction is kept warm for 1-2 hours, it is naturally cooled to room temperature to complete the heat treatment operation; in step B2, the amount ratio of the composite silicon nitride fiber, 98.0wt% sulfuric acid and sodium chlorate is 5-6g:50-60mL:3-5g.
6. The wear-resistant and corrosion-resistant refractory material for hazardous waste incinerator according to claim 1, characterized in that: The preparation method of the high temperature adhesive comprises the following steps: C1. Add 2,4,6,8-tetramethyl-2-[3-(oxiranylmethoxy)propyl]cyclotetrasiloxane, 3-(methacryloyloxy)propyltrimethoxysilane, epoxy vinyl resin, chloroplatinic acid hexahydrate and N,N-dimethylformamide into a reaction kettle, increase the temperature of the reaction kettle to 40-50° C., keep the temperature for reaction for 1-2 hours, and perform post-treatment to obtain a composite resin; C2. Add the composite resin, silicone resin and N,N-dimethylformamide into the reactor. After the temperature of the reactor is lowered to 0-5°C, add saturated sodium hydroxide solution dropwise into the reactor. After keeping the temperature for 1-2 hours, adjust the pH value of the system to 7 with glacial acetic acid, and obtain the adhesive precursor by post-treatment. C3. The adhesive precursor, the composite silicon nitride fiber and the activated silicon nitride fiber are mixed evenly and added into a twin-screw extruder for melt extrusion to obtain a high-temperature adhesive.
7. The wear-resistant and corrosion-resistant refractory material for hazardous waste incinerator according to claim 6, characterized in that: In step C1, the amount ratio of 2,4,6,8-tetramethyl-2-[3-(oxiranylmethoxy)propyl]cyclotetrasiloxane, 3-(methacryloyloxy)propyltrimethoxysilane, epoxy vinyl resin, chloroplatinic acid hexahydrate and N,N-dimethylformamide is 8-10g:3-4g:10-15g:0.1-0.2g:80-100mL; in step C2, the amount ratio of composite resin, silicone resin, N,N-dimethylformamide and saturated sodium hydroxide solution is 3-4g:5-8g:30-40mL:0.1-0.2mL; in step C3, the amount ratio of adhesive precursor, composite silicon nitride fiber and activated silicon nitride fiber is 8-10g:1g:1g.
8. The wear-resistant and corrosion-resistant refractory material for hazardous waste incinerator according to claim 1, characterized in that: The preparation method of the high-alumina aggregate is as follows: high-alumina bauxite is crushed through a 400-600 mesh screen, mixed with nanocrystalline liquid, and then transferred to a tubular furnace, and calcined to obtain the high-alumina aggregate.
9. The wear-resistant and corrosion-resistant refractory material for hazardous waste incinerator according to claim 8, characterized in that: The dosage ratio of high-alumina bauxite and nanocrystalline liquid is 2-3g:1mL, and the calcination operation is as follows: after nitrogen protection is introduced into the tubular furnace, the tubular furnace is heated to 1350-1600°C at a heating rate of 5-8°C / min, the reaction is kept warm for 4-6h, and naturally cooled to room temperature to obtain high-alumina aggregate.
10. The method for preparing a wear-resistant and corrosion-resistant refractory material for a hazardous waste incinerator according to claims 1-9, characterized in that: The following steps are involved: High-alumina aggregate, boron nitride powder and steel fiber are added to a twin-screw extruder. Composite aerogel, high-temperature adhesive and water glass are gradually added to the mixture during stirring. The pressure of the twin-screw extruder is set to 80-100 bar. After twin-screw extrusion, wear-resistant, corrosion-resistant and refractory materials are obtained.
Citation Information
Patent Citations
Fireproof material
CN108975887A
High-temperature-resistant thermal insulation material and preparation method thereof
CN111848106A
Multi-base composite low-heat-conduction refractory brick for garbage incinerator
CN115160001A
Refractory aerogel composite thermal insulation material and preparation method thereof
CN115849863A
Refractory material resistant to high-temperature HC1 gas corrosion and preparation method
CN117510214A